"Como se fora brincadeira de roda": o grupo colaborativo como mediador do desenvolvimento docente - Pedro, Luciana Guimarães (2019)
Considering the numerous challenges faced by teachers in their professional performance, the present research, carried out within the scope of the Research on Educational Knowledge and Practices, had as its theme the professional teacher development of teachers. With the objective of goal to learn and to analyze the process of professional teacher development in the movement of a collaborative group, we carried out an university extension course as a proposal for continuing education, aimed at the licensed teachers who work in Basic Education II and High School in the municipal and state public schools of the municipality of Uberlândia and its surroundings, with up to six years of professional experience. The collaborative group that counted with the participation of eleven teachers who met weekly, during sixteen reflective sessions with an average duration of three and a half hours each. For the development of this training proposal, we take as a basis: the knowledge of Education that understands teaching as a profession that is constituted throughout the life of the teacher; the principles of Historical-Cultural Theory and its concepts that help us to understand our goal of study; the discussions about the schooling process promoted by the School and Educational Psychology on a critical part and the orientations brought by the Collaborative Research. Thus, we built a collaborative group that counted with the participation of eleven teachers who met weekly, during sixteen reflective sessions with an average duration of three and a half hours each. The sharing, dialogues and records built in the movement of the collaborative group constituted the corpus of research that was analyzed according to the proposal of the Core of Meaning, through which we defined eight indicators of analysis that showed: 1) signs of transformation in the beliefs and conceptions of teachers; 2) indications of re-signification of knowledge; 3) indications of construction of new pedagogical practices; 4) evidence of the construction of professional identity; 5) indications of the importance of affectivity in the world of teaching; 6) signs of crisis in teaching; 7) evidence that the collaborative group is a promoter of development and 8) evidence of professional teacher development. We articulate these indicators to the scientific knowledge that grounded the research theoretically and define three core of meaning that sought to analyze: the mediation in the context of the collaborative group; the dramas and transformations experienced by the collaborating teachers and the specificities of the collaborative group and its the repercussion in the process of professional teacher development. As conclusive syntheses, we argue that the group built on the basis of the Collaborative Research guidelines and in the knowledge of School and Educational Psychology on a critical part has consolidated itself as a relevant mediator to the development of teachers; that the development process of the teacher has as an important engine the mediation of the others and the dramas experienced by teachers; that the pedagogical decisions guided by affectivity determine the quality of the bond established in the group contexts and, consequently, the processes of learning, transformation and development experienced by its collaborators. Finally, we present some presupposition to inspire the construction and conduction of collaborative groups as a proposal of continuous formation for teachers, emphasizing that professional development is an aspect of human development that can have in the collaborative group a useful space for the construction of collaborative and fraternal partnerships aimed at the emancipation and transformation of the human, education and society.